2021
DOI: 10.1016/j.jbc.2021.101207
|View full text |Cite
|
Sign up to set email alerts
|

Structural and kinetic analyses of holothurian sulfated glycans suggest potential treatment for SARS-CoV-2 infection

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(99 citation statements)
references
References 104 publications
6
93
0
Order By: Relevance
“…The ideal anti-SARS-CoV-2 marine sulfated glycan would be devoid of anticoagulant effects ( 67 ). The native BoSG, a hydrolyzed unfractionated BoSG sample (SGhd) and the four fractions of different MWs derived from BoSG (Fr1-Fr4) were subjected to in vitro anticoagulant assays to investigate the impact of MW on the anticoagulant action of BoSG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ideal anti-SARS-CoV-2 marine sulfated glycan would be devoid of anticoagulant effects ( 67 ). The native BoSG, a hydrolyzed unfractionated BoSG sample (SGhd) and the four fractions of different MWs derived from BoSG (Fr1-Fr4) were subjected to in vitro anticoagulant assays to investigate the impact of MW on the anticoagulant action of BoSG.…”
Section: Resultsmentioning
confidence: 99%
“…A heparin disaccharide was also constructed and docked for comparison. The binding site examined in this study was the same one previously used for the holothurian sulfated glycans in binding analyses to the wild type and the N501Y mutant S-protein RBDs ( 67 ). The docking data are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that sulfated polysaccharides inhibit the interaction between HS and the S-protein, including heparin, fucoidans, and rhamnan sulfate [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 92%
“…Finally, an in vitro SARS-CoV-2 pseudotyped viral particle neutralization assay was performed. Sulfated glycans such as heparin have been shown to inhibit viral infection by interacting with the SARS-CoV-2 spike protein [24][25][26][27]. Thus, we investigated the ability of PPS and MPS to inhibit viral particle entry using a cell-based neutralization assay.…”
Section: In Vitro Sars-cov-2 Pseudotyped Viral Particle Neutralizationmentioning
confidence: 99%